Co3O4-Based Materials as Catalysts for Catalytic Gas Sensors - Olena Yurchenko; Patrick Diehle; Katrin Schmitt; Jürgen Wöllenstein (Proceedings)
The work deals with the development of Co3O4-based catalysts for application in catalytic gas sensors. Among the transition-metal oxide catalysts, cobalt oxide exhibits the highest activity in catalytic combustion. The catalytic activity of the catalysts was examined by Differential Scanning Calorimetry (DSC), evaluating the catalyst’s activity by measuring its thermal response to 1% methane (CH4).